Multicentre, randomised, double blind, placebo controlled, phase III study of weekly, low dose, subcutaneous interferon beta-1a in secondary progressive multiple sclerosis. Issue 5 (16th April 2004) - Andersen, O; Elovaara, I; Färkkilä, M; Hansen, H J; Mellgren, S I; Myhr, K-M; Sandberg-Wollheim, M; Soelberg Sørensen, P
Abstract : Objective: Interferon (IFN) beta has repeatedly shown benefit in multiple sclerosis (MS) in reducing the rate of relapse, the disease activity as shown with magnetic resonance imaging and, to some degree, the progression of disability; however, it is unknown how much the therapeutic response depends on the dose, the subgroup involved, and the disease stage. This multicentre, double blind, placebo controlled study explored the dose−response curve by examining the clinical benefit of low dose IFN beta-1a (Rebif®), 22 μg subcutaneously once weekly, in patients with secondary progressive MS. Methods: A total of 371 patients with clinically definite SPMS were randomised to receive either placebo or subcutaneous IFN beta-1a, 22 μg once weekly, for 3 years. Clinical assessments were performed every 6 months. The primary outcome was time to sustained disability, as defined by time to first confirmed 1.0 point increase on the Expanded Disability Status Scale (EDSS). Secondary outcomes included a sensitive disability measure and relapse rate. Results: Treatment had no beneficial effect on time to confirmed progression on either the EDSS (hazard ratio (HR) = 1.13; 95% confidence interval (CI) 0.82 to 1.57; p = 0.45 for 22 μg v placebo) or the Regional Functional Status Scale (HR = 0.93; 95% CI 0.68 to 1.28; p = 0.67). Other disability measures were also not significantly affected by treatment. Annual relapse rate was 0.27 with placebo and 0.25 with IFN (rate ratio = 0.90; 95% CI 0.64 to 1.27; p = 0.55). The drug was well tolerated with no new safety concerns identified. No significant gender differences were noted. Conclusions: This patient population was less clinically active than SPMS populations studied in other trials. Treatment with low dose, IFN beta-1a (Rebif®) once weekly did not show any benefit in this study for either disability or relapse outcomes, including a subgroup with preceding relapses. These results add a point at one extreme of the dose−response spectrum of IFN beta therapy in MS, indicating that relapses in this phase may need treatment with higher doses than in the initial phases.